FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Sutandi Sutandi (Universitas Muhammadiyah Tangerang, 2020)
The purpose of this study was to determine the factors that influence the value of the company in banking companies listed on the Indonesia Stock Exchange (IDX). The research period used was 6 years, namely the period 2013-2018.The population of this study includes all banking sectors listed on the Indonesia Stock Exchange (IDX) in the period 2013-2018. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained a sample of 27 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. In this study the data analysis method used is multiple linear regression analysis.The results showed that partially Investment Decision, Dividend Policy, Capital Structure, Leverage, Profitability, and Company Size significantly influence Company Value, while simultaneously Investment Decisions, Dividend Policy, Capital Structure, Leverage, Profitability, and Company Size also significantly influence on Company Value.